Проблемы в становлении гендерной идентичности спортсменок в традиционно мужских видах спорта - Baranova A. V. (Pedagogy and psychology: development prospects, 2018)
The article touches gendernoy authentication of sportswomen in those types of sport, which are traditionally considered masculine. The circle of types of sport which accustoms women broadens constantly. However attitude of society toward it not simply, that tells on the psychological state of sportswomen. Probably, specific psychological accompaniment can be required them.
Keywords: маскулинность; гендерная идентичность; masculinity; феминность; femininity; female athletes in tradition masculine sports; difficulties in gender identity development; мужские виды спорта